Research in social problems and public policy : William R. Freudenburg, A life in social research (Bingley : Emerald Group Publishing, 2013)
"A research annual."
Includes bibliographical references.
Also issued online.
SERBIB/SERLOC merged record
Keywords: Sociology -- Periodicals; Social problems -- Periodicals; Social policy -- Periodicals; Social policy; Social problems; Sociology; Public Policy; Research; Social Problems; United States; Periodicals; Periodicals; Periodicals